Design principles of a light, wearable upper limb interface for prosthetics and teleoperation - Castellini, Claudio (Wearable Robotics - Systems and Applications, 2019)
In this chapter we propose and discuss a few guidelines for the design, implementation, and testing of a lightweight, wearable human-machine interface aimed at control of upper limbs-be they tele-operated robotic arms or prosthetic devices. While reviewing the state of the art in the field we highlight the current pitfalls, then suggest how to overcome them: what sensors to use, how to safely and effectively attach them to a human body, and how to design, monitor, and exploit a fruitful man-machine interaction. The result is a collection of requirements for, and ways to build, a device which can be worn in everyday living, and whose computation can happen on a smartphone, which would enable both intact and amputated persons to control a robotic arm/hand system.
CRIS-Team Scopus Importer:2021-09-13
Keywords: Wearable sensors; teleoperation; rehabilitation robotics; assistive robotics; incremental machine learning; interactive machine learning; human–robot interaction; intent detection; motion tracking